An overview of dysphagia rehabilitation for stroke patients - Klayne Cunha Matos; Vanessa Fernandes de Oliveira; Paula Luanna Carvalho de Oliveira; Pedro Braga Neto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Dysphagia is characterized by difficulty in the swallowing pattern at any stage of this neuromuscular process. It is a frequent symptom after stroke. Objective: This study aimed to investigate the most commonly used phonoaudiological interventions as therapy for the treatment of swallowing disorders in patients with dysphagia after stroke. Methods: We performed a review of studies indexed in MEDLINE-PubMed, LILACS, Cochrane, and Clinical trials.gov focusing on speech-language interventions for adult dysphagic patients after stroke between January 2008 and January 2021. Results: Thirty-six articles of clinical trials were selected. Eleven different types of therapies have been studied. Studies on the efficacy of therapeutic interventions for the rehabilitation of adult patients with dysphagia after stroke are still scarce. Most techniques are combined with conventional therapy, so the effectiveness of the other techniques alone cannot be assessed. Conclusions: Therapeutic interventions should be selected in accordance with the possibilities and limitations of the patients, and especially with the findings of the clinical evaluation and with its objective.